The Interface of Nutrition and Immunity: An in-depth look at nutritional interventions for the oncology patient receiving immunotherapy - Al Rowaili, Saad Laiban B; Alshiak, Ali Saeed Al; Al khamis, Abdullah Esse; Al Shggag, Adel Abdullah; Alotaibi, Eman Ghannam; Alenazi, Maha Shreedah; Al-Dosiry, Dalal Mohmmed; Albdiawy, Azhar Ali; A Alrajal, Mohammed Ibrahim; Alsaeed, Abdullatif Abdulrhman; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Immunotherapy, as immune checkpoint inhibitors (ICIs), has revolutionized oncology by taking advantage of the patient’s native immune system to combat cancer. Although responses are heterogeneous, immune-related adverse events (irAEs) can limit treatment benefit and decrease quality of life. A growing appreciation is arising that host factors, including nutritional status and diet, play an important role in determining the immune response and tumor microenvironment. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The objective of this review is to provide an overview of the current evidence relating to nutritional strategies in cancer immunotherapy patients. It considers the ruinous role of malnutrition (cachexia) in clinical outcomes, reviews the mechanisms by which particular dietary components influence anti-tumor immunity and treatment side effects, and provides a model for the practical assessment and management of nutritional deficits. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> A systematic review of the literature was conducted through the utilization of leading scientific databases (e.g., PubMed, Scopus, Web of Science) to identify preclinical, clinical, and review articles published up to 2024. Search terms were permutations of "immunotherapy," "immune checkpoint inhibitors," "nutrition," "diet," "cachexia," "microbiome," and "immune-related adverse events." The evidence was synthesized to provide a narrative review of the existing literature. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> There is evidence that indicates that sarcopenia and malnutrition have a close correlation with poorer efficacy of ICI and increased toxicity. Individual nutritional interventions are promising for modulating outcomes: adequate consumption of good-quality protein is crucial for the avoidance of muscle wasting and immune function maintenance; dietary fiber and omega-3 fatty acids exert anti-inflammatory effects and preserve a healthy gut microbiome; the Mediterranean diet and vegetarian dietary patterns are related to improved survival; and micronutrients like Vitamin D have a role in immune regulation. The gut microbiome is identified as a mediator between diet and immunotherapy response. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> An active, individualized nutrition approach, emphasizing a whole-food, plant-based diet, adequate protein, specific micronutrients, and gut microbiome support, is very promising as an adjunctive strategy to enhance the efficacy and tolerability of immunotherapy. Further robust, prospective clinical trials are needed to solidify specific recommendations and integrate nutritional therapy into the standard armamentarium of immuno-oncology treatment.